Biomanufacturing design: reducing the environmental burden. (August 2022) - Whitford, Bill; Jones, Daniel; Kinnane, Sean
Abstract : Biopharmaceutical manufacturing provides products yielding value in human health. Nevertheless, many desire to reduce its environmental footprint with science-based approaches to environmental burden reduction, and a rational design of solutions. Pharmaceutical suppliers, academia, and service providers are cooperating to, for example, define and educate those concerned regarding the paths to more circular economies throughout the product life cycle. They accomplish this by establishing new sustainability programs, certifications, personnel positions, initiatives, and in-service training. They are also promoting sustainability through publications, foundation donations, and consortia support. Experienced architectural and process design sponsors now orchestrate materials, processes, and suite designs to support economical reductions in many categories of environmental stress — as well as to meet relevant client, societal, and regulatory expectations.